Sovereignty by Design: Embedding Fiscal Risk Intelligence in Europe’s Defence-Digital Strategy - Bierecki, Dominik; Czuryk, Małgorzata; Gaie, Christophe; Langlois-Berthelot, Jean (PRAWO i WIĘŹ, 2026)
The European Union confronts structural uncertainty across defence and digital sectors. Fiscal governance still relies on stability-oriented frameworks that cannot handle volatility. This paper argues that strategic autonomy requires integrating actuarial reasoning – quantification, pricing and systemic treatment of uncertainty – into existing EU budgeting and investment tools. The approach does not require new institutions or treaty changes. It requires a change in decision logic inside the Multiannual Financial Framework, the European Defence Fund, the Digital Europe Programme and the European Investment Bank. Empirical work in cyber-risk insurance, cyber-threat forecasting and development finance demonstrates that uncertainty can be modelled and priced. Actuarial governance emerges as a necessary foundation for credible European sovereignty.